THE ROLE OF TATTOOS IN PRISON COMMUNITY - Ana Batrićević (Revija za kriminologiju i krivično pravo)
With their roots set deep in the tradition of many different cultures, carrying the mark of social stigma throughout the early ages of modern prison systems development, and finally, becoming fashion accessories inseparable from modern pop culture, tattoos obtain a rather specific meaning if made behind the prison walls. There are several reasons for that: their symbolism, the roles they have inside the prison community, their relation to criminal behaviour, their impact on offender’s re-socialization and re-offending as well as the health risks they cause. Having in mind the worldwide presence of this phenomenon and its local manifestations, the authors of this paper analyse its socio-genesis, taxonomy, functions and consequences as well as potential responses aimed at mitigating the negative impacts of prison tattoos on the life, health and reintegration of offenders.